PROTECTIVE EFFECTS OF CRUDE FLAVONOIDS AND ALKALOIDS EXTRACTS OF MATRICARIA CHAMOMILLA L. IN CHICKS AGAINST PENTYLENETETRAZOLE-INDUCED CONVULSIONS - SULEIMAN, SULEIMAN DAWOOD; HASSAN, JIAN SALAM (Journal of Duhok University, 2023)
The current study was carried out to assess the anticonvulsant and antioxidant effects of crude flavonoids and alkaloids extracts of Matricaria chamomilla L. against pentylenetetrazol (PTZ) induced convulsions in chicks. Seventy-two chicks of either sex were randomly divided into 6 groups (each group n=12). The groups were treated with normal saline, PTZ (90 mg/kg, subcutaneous injection, sodium valproate (200 mg/kg, orally), oral administration of crude flavonoids and intraperitoneal injection of crude alkaloids extracts (20, 40, 80 mg/kg) respectively. After treatment with sodium valproate and the crude extracts, the animals were treated with PTZ and observed for 30 minutes for convulsion signs. Subsequently, the brain and blood samples were collected for biochemical estimation of gamma-aminobutyric acid (GABA) and glutamate in the brain tissue, as well as catalase, glutathione reductase, malondialdehyde, 8-isoprostane, some electrolytes (potassium, sodium, chloride, ionized calcium, total calcium), pH, and glucose levels in the serum. The group pretreated with the highest doses (80 mg/kg) showed a significant increase in GABA, and a decrease in glutamate in the brain tissue. Additionally, there was a significant increase in catalase, and a significant decrease in malondialdehyde, 8-isoprostane, and an increase in sodium and ionized calcium ions concentration in the serum. It was concluded that a combination treatment of crude flavonoids extract with crude alkaloids extract attenuated the convulsions and oxidative stress induced by PTZ in chicks.